Tiga Dara & Ini Kisah Tiga Dara: Feminisme dalam Film - Sentosa, Karin (Sekolah Pascasarjana Institut Kesenian Jakarta, 2019)
Films on women’s issues are more and more frequent in theatres in line with the popularity of feminism in pop culture, especially in Indonesia. Two films Tiga Dara (1956) directed by Usmar Ismail was remade using the title Ini Kisah Tiga Dara (2016) directed by Nia Dinata. These two films describe similar conflict of marriage experienced by women in urban areas with different time setting. This research will compare those two films in terms of their structure and meaning based on the perspective of feminism. Through the comparison, it is revealed that the difference is on shifting of meaning and how the films convey the message. Other than that, the concept on women also change: the experience of women in every class, race, age, and sexuality is subjective depending on each individual. By delving in the way women are personified in the two films, we will find what the concept of women film is all about.Film tentang perempuan semakin banyak digarap oleh sutradara Indonesia seiring semakin populernya feminisme dalam budaya populer, khususnya di Indonesia. Film Tiga Dara (1956) karya Usmar Ismail dibuat-ulang dengan judul Ini Kisah Tiga Dara (2016) oleh Nia Dinata. Kedua film ini berisi konflik sama yang dialami perempuan di perkotaan dengan latar belakang zaman yang berbeda yaitu pernikahan. Penelitian ini membandingkan kedua film tersebut secara struktural dan makna menggunakan perspektif feminisme. Melalui perbandingan tersebut, ditemukan adanya perubahan makna dan cara penyampaiannya yang bergeser. Selain itu, konsep mengenai perempuan juga berubah: pengalaman perempuan di setiap kelas, ras, umur, dan seksualitas bersifat subjektif tergantung tiap individu. Dengan melihat bagaimana perempuan dipersonifikasi dalam kedua film tersebut, dapat diketahui bagaimana konsep film perempuan